Implementing Organizational WHP Into Practice: Obstructing Paradoxes in the Alignment and Distribution of Empowerment - Skagert, Katrin; Dellve, Lotta (Frontiers in Public Health, 2020)
Background: According to policy and theory, there is need for organizational workplace health promotion (WHP) to strengthen working conditions for all employees. However, earlier studies show it is hard to implement in practice. The aim was to critically analyze and identify interacting mechanisms and obstacles behind failures of organizational WHP projects from system perspectives. Methods: A holistic case study was performed, to critically analyze data from an organizational WHP project approach at a public health care organization. The qualitative data was collected over five years and included interviews with key actors (n=80), focus groups (n=59 managers), structured observations (n=250 hours), continuous field observations and documents (n=180). Questionnaires to employees (n=2974) and managers (n=140) was complementing the qualitative-driven mixed method approach. Results: The analysis shows obstructing paradoxes of alignment and distribution of empowerment during the process of implementation into practice. The obstacles were interacting over system levels and were identified as: Governance by logics of distancing and detaching, No binding regulation of WHP, Separated responsibility of results, Narrow focus on delegated responsibilities, Store-fronting a strategic model, Keeping poor organizational preconditions and support for developments and Isolate WPH from other organizational developments. Conclusions: The following premises can be formulated regarding successful organizational WHP programs. Consider (1) the uncertainty a distributed empowerment to all system levels may create; (2) the distributed impact to define the target and allow broader areas to be included in WHP; and (3) the integration into other development processes and not reducing the organizational WHP to the form of a project.